Concord and DP Structure in Bafut - Tamanji, Pius N. (AAeO - Afrikanistik-Aegyptologie-Online, 2006)
This article accounts for DP-internal concord phenomena in Bafut [2] while at the same time characterizing the internal structure of the Bafut DP in the light of various word order patterns displayed. In the Bafut DP, all arguments and satellites follow the head noun (except when focused) and agree with it in number and gender/class. The following examples illustrate the various word order and concord patterns. In these, and subsequent examples, figures in the glosses indicate noun class.